Imam Al-Shafi'i's Thought About Human Obligations and Rights in Islamic Law - Rizal, Muhammad; Bahri, Abdul Halem (Universitas Islam Negeri Alauddin Makassar, 2022)
Human rights are topics that are constantly debated without a unified definition. Therefore, this study aimed to analyze human rights from the perspective of the Imam school of thought by using the analysis of Imam Al-Shafi’i. It adopted a qualitative approach using the library research method based on data management obtained from several pieces of literature. Furthermore, this study used a normative approach by adapting several books by Imam Al-Shafi’i. According to Imam Al-Shafi’I, human obligations and rights in Islamic law are inseparable, and Muslims should examine the past to comprehend the origins and evolution of these concepts. In addition, human rights are a basic concept, as seen in Al-Umm and Al-Risālah. These texts are quite unconventional for people to study human rights. The work and application imposed by Imam Al-Shafi’i are not different from what is explained by several figures of thinkers from the West. The application found a match after seeing several figures’ development of human rights thought. Therefore, contemporary Muslim scholars should prioritize the issue of human obligations and rights in providing legal solutions.